Long term effects of a combined physical conditioning and fencing training program on neuromuscular performance in elite fencers - Tsolakis, C.; Katsikas, C. (International Journal of Fitness, 2003)
The aim of the present study was to evaluate the effects of a long-term physical conditioning program primarily focused on power development combined with a typical fencing training on selected neuromuscular parameters of elite Greek fencers. Five men and four women, all members of the Olympic team aged 21.9±2.4y, height 176.7±8.3 cm and weight 67.5±12.3 kg participated in this study. The jumping ability (squat, countermovement and drop jump) and the leg cross sectional area (CSA) were measured in six different occasions according to their annual periodization program. The contact time of the drop jump was significantly different between the training phases (F=5.49, p<0.000). There was not any significant relation between dominant- non dominant leg cross sectional areas (CSA) and jumping performance in any training phase. The significant improvement in contact time without any significant change in legs CSA of this study suggests that the observed differences in contact time were probably attributed to neural training effects. A long term physical conditioning program in combination with training for the sport specific tasks has proved useful influencing the neuromuscular performance of elite fencers.